Response of gross ecosystem product to land use change in an area with intersecting water systems in southwestern China - Ma, Shibin; Zhou, Zhongfa; Zhang, Yongrong; Dong, Chao; Zhang, Cheng (Frontiers in Environmental Science, 2025)
IntroductionAs an important ecological barrier and major water source in the upper reaches of the Yangtze and Pearl Rivers, the Zhongshan District, Guizhou Province, Southwest China, is of great ecological significance. The gross ecosystem product (GEP) of the area not only reflects the overall condition of the ecosystem but also provides an important basis for regional ecosystem service management and scientific decision-making by quantifying nature’s contribution to human society.MethodsThrough systematic analysis of the land use changes between 2000 and 2020, calculated the GEP for 2000, 2005, 2010, 2015, and 2020. In addition, based on the elasticity index, the impact of land use change on the spatial differentiation of the GEP was further clarified at the raster scale.ResultsThe results show that (1) between 2000 and 2020, the main land use types in the study area were dominated by forests, grassland, and agriculture; and the urban areas changed significantly, mainly reflecting the transition between urban land, water bodies, grassland, and shrubland. (2) The GEP exhibited an overall increasing trend in the study area from 2000 to 2020. In terms of the structure of the GEP, 2000–2015 was dominated by regulating services, which mainly manifested in climate regulation, soil and water conservation, flood control, and water conservation; while 2015–2020 was dominated by product provision services, which mainly manifested in agricultural products. (3) From 2000 to 2020, the main contribution of the land use changes to the GEP growth was the increase in the area of the human-exploited wetlands and the transfer of forest, grassland, and shrubland to cropland.DiscussionThe quantitative analysis of the elasticity coefficient further demonstrates that small changes in wetlands and cropland can lead to significant changes in the GEP. These results highlight the importance of incorporating key factors such as the anthropogenic activity intensity and agricultural cropping structure and area in management decisions for ecosystems in the study area.